Comparative Utility of Transient and 2D Shear Wave Elastography for the Assessment of Liver Fibrosis in Clinical Practice. - Karagiannakis, Dimitrios S.; Voulgaris, Theodoros; Angelopoulos, Theodoros; Ioannidou, Panagiota; Cholongitas, Evangelos; Vlachogiannakos, Jiannis; Papatheodoridis, George V. (Journal of Digital Imaging, 2021)
The aim of the study was to investigate the feasibility and correlation of liver stiffness measurements (LSM) between 2D-shear wave elastography (2D-SWE) and transient elastography (TE) in patients with chronic liver disease. Over 4 months, 421 patients with chronic liver disease of any cause underwent LSM by 2D-SWE and TE (M and/or XL probe) and controlled attenuation parameter at the same visit. LSM was not feasible by TE in 16 (3.8%) and by 2D-SWE in 17 (4.0%) patients. Median LSM were 8.9 and 8.7 kPa with TE and 2D-SWE, respectively, having a strong correlation (r = 0.774, p < 0.001) in the total cohort and in any cause of liver disease (r = 0.747–0.806, p < 0.001). There was a strong agreement on diagnosis of severe fibrosis (k-statistic: 0.841, p < 0.001) or cirrhosis (k-statistic: 0.823, p < 0.001). Both methods had increased failure rates in patients with obesity and/or increased waist circumference. Among 104 obese patients, TE was more feasible than 2D-SWE (92.3% vs 85.6%, p < 0.001]. LSM by 2D-SWE are strongly correlated to LSM by TE independently of the etiology of chronic liver disease, stage of fibrosis, degree of liver steatosis, and patients' characteristics. TE with the XL probe may be superior in a minority of obese patients.